Oral Prescription Opioids as a High-Risk Indicator for Hepatitis C Infection: Another Step Toward HCV Elimination - Benjamin Hack; Utsav Timalsina; Eshetu Tefera; Brittany Wilkerson; Emily Paku; Stephen Fernandez; Dawn Fishbein (SAGE Publishing, 2021)
Background The opioid epidemic across the U.S. poses an array of public health concerns, especially HCV transmission. HCV is now widely curable, yet incident rates are increasing due to the opioid epidemic. Despite the established trajectory from oral prescription opioids (OPOs) to opioid use disorder (OUD), OUD to injection drug use (IDU), and IDU to hepatitis C virus (HCV), OPOs are not a defined risk factor (RF) for HCV infection. The objective of this study was to observe rates of HCV testing and Ab reactivity (HCVAb+) in patients receiving OPOs to substantiate them as a RF, ultimately contributing to HCV elimination. Methods Data from MedStar Health patients receiving OPOs from 1/2017 to 12/2018 were collected and analyzed using chi-squared or student t -tests and logistic regression for uni- or multi-variable analyses, respectively. Statistical significance was defined as P  < .05; Epi Info and SAS v 9·4 were used for statistical analyses; IRB approval was received. Results There were 115 415 individuals prescribed OPOs over the study period. In this population, 8.6% (932) were HCVAb+ when tested and not previously diagnosed (10 900); 3.4% (3893) had an OUD diagnosis, 20.6% (803) of whom were HCV tested; 25.4% (361) of all HCVAb+ (1421) had an OUD diagnosis. OUD (ORadj 8.53 [7.22-10.07]) was an independent predictor of HCVAb+ in this population. Conclusions (1) In a large population prescribed oral opioids, HCVAb+ was 8.6%, higher than our previously published data (2.5%) and the US rate (1.7%); (2) only 20% of patients diagnosed with OUD were tested; and (3) only 25% of HCVAb+ patients were classified with OUD; this suggests underreporting of OUD in this population. Primary Care and Community Health Recommendations: (1) Re-testing for HCV in patients taking OPOs; (2) increased HCV testing among OUD patients; and (3) improved surveillance and reporting of OUD.